Islamic Religious Education (PAI) Learning in Developing Environmental Theology at Muhammadiyah 3 Elementary School Bandung - Muhammad Sigit Muthahhari (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
Islamic Religious Education (PAI) holds a strategic role in developing ecological awareness and environmental theology among the younger generation. This study aims to explore how the integration of ecological values in PAI learning at Muhammadiyah 3 Elementary School Bandung can enhance environmental awareness and shape students’ character to be responsible for environmental sustainability. Using a descriptive qualitative approach, this research analyzes the application of environmental theology in PAI learning through observation, interviews, and documentation. The findings show that teaching ecological values in Islam, such as the concept of khalifah fil ardh (humans as stewards of the earth) and amanah (trust), has been integrated into various learning activities, both inside and outside the classroom. Project-based learning methods and practical activities such as the Friday Clean-Up Movement, the School Waste Bank, the Green Class Project, and Tadabbur Alam (nature contemplation) have proven effective in fostering students’ ecological awareness. The role of PAI teachers as ecological role models is also crucial in reinforcing these values. This research provides an important contribution to designing a PAI curriculum that is more responsive to environmental challenges and aligned with Islamic principles that emphasize a harmonious relationship between humans and nature.